2018
DOI: 10.1097/md.0000000000013660
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of the loop-mediated isothermal amplification assay for the detection of common lower respiratory pathogens in patients with respiratory symptoms

Abstract: Lower respiratory tract infections (LRTIs) are a substantial public health problem and a leading cause of significant morbidity and mortality worldwide. The aim of this study was to evaluate a commercially available loop-mediated isothermal amplification (LAMP) assay for the simultaneously detection of thirteen common lower respiratory pathogens in patients with respiratory symptoms. All participants age from 1 to 101 years old were recruited from inpatient or outpatient of Meizhou People's Hospital between Oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…Among various microfluidic technologies, such as hydrophilic–hydrophobic patterning [9] , [10] , the SlipChip [11] , [12] , [13] , [14] , and electrowetting-on-dielectric (EWOD) technology [15] , [16] , the centrifugal-based method offers the advantages of simple operations, fully enclosed microstructures, and easy integration with other microfluidic functions [17] , [18] . Our group previously developed a disc-shaped centrifugal microdevice operated in a compact instrument with a single channel (only one sample tested per run) and proved the excellent multiplexing capability of this system by demonstrating the detection of 13 respiratory pathogenic bacteria using loop-mediated isothermal amplification (LAMP) on a single chip [19] . However, when viruses are detected, neither RT-PCR nor LAMP are amenable for use with a microchip due to thermal cycling and primer design problems, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Among various microfluidic technologies, such as hydrophilic–hydrophobic patterning [9] , [10] , the SlipChip [11] , [12] , [13] , [14] , and electrowetting-on-dielectric (EWOD) technology [15] , [16] , the centrifugal-based method offers the advantages of simple operations, fully enclosed microstructures, and easy integration with other microfluidic functions [17] , [18] . Our group previously developed a disc-shaped centrifugal microdevice operated in a compact instrument with a single channel (only one sample tested per run) and proved the excellent multiplexing capability of this system by demonstrating the detection of 13 respiratory pathogenic bacteria using loop-mediated isothermal amplification (LAMP) on a single chip [19] . However, when viruses are detected, neither RT-PCR nor LAMP are amenable for use with a microchip due to thermal cycling and primer design problems, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…We searched PubMed database for articles with the keywords “LAMP, pneumonia or lower respiratory tract infections.” There was no language restriction, and COVID-19 was removed. We found three results ( Hou et al, 2018 ; Scharmann et al, 2020 ; Wang et al, 2020 ), all three of which collected respiratory tract specimens and submitted them for LAMP and routine clinical pathogenic testing, but did not confirm and interpret the controversial results from a clinical perspective. The indicators detected by LAMP technology are limited to 2–9 kinds of bacteria, and no attention was paid to the elderly.…”
Section: Discussionmentioning
confidence: 86%
“…20173401346). Their previous data found that compared with DNA sequencing, the sensitivity and specificity of CCID are over 95 and 99%, respectively ( Hou et al, 2018 ). However, the application value of CCID has not been verified by rigorous clinical studies.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the percentages of bacterial pathogen infection with MRSA patients have systemic disease (21.9%) was relatively higher than patients without systemic disease group (P = 0.001). MRSA is the most common bacterial pathogen infection that gives rise to a high burden of signi cant healthcare costs, morbidity, and mortality for patients every year [24][25][26]. The percentages of bacterial pathogen infection with P. aeruginosa tested positive made up 9.4% among patients with systemic disease group (P = 0.029).…”
Section: Discussionmentioning
confidence: 99%